Exploring the therapeutic potential of endolysin CD27L_EAD against Clostridioides difficile infection - Cho, Youngjin; Park, Kyungah; Park, Jeongseok; An, Jieun; Myung, Heejoon; Yoon, Hyunjin (International Journal of Antimicrobial Agents, 2024)
Objectives: Clostridioides difficile has emerged as a major cause of life-threatening diarrheal disease. Conventional antibiotics used in current standards of care exacerbate the emergence of antibiotic-resistant strains and pose a risk of recurrent C. difficile infection (CDI). Thus, there is an urgent need for alternative therapeutics that selectively eliminate C. difficile without disturbing the commensal microbiota. This study aimed to explore the potential of endolysins as an alternative therapeutic agent to antibiotics. Endolysin is a bacteriophage-derived peptidoglycan hydrolase that aids in the release of phage progeny during the final stage of infection. Methods: In order to exploit endolysin as a therapeutic agent against CDI, the bactericidal activity of 23 putative endolysins was compared and ΦCD27 endolysin CD27L was selected and modified to CD27L_EAD by cleaving the cell-wall binding domain of CD27L. Results: CD27L_EAD exhibited greater bacteriolytic activity than CD27L and its activity was stable over a wide range of salt concentrations and pH conditions. CD27L_EAD was added to a co-culture of human gut microbiota with C. difficile and the bacterial community structure was analyzed. CD27L_EAD did not impair the richness and diversity of the bacterial population but remarkably attenuated the abundance of C. difficile. Furthermore, the co-administration of vancomycin exerted synergistic bactericidal activity against C. difficile. β-diversity analysis revealed that CD27L_EAD did not significantly disturb the composition of the microbial community, whereas the abundance of some species belonging to the family Lachnospiraceae decreased after CD27L_EAD treatment. Conclusions: This study provides insights into endolysin as a prospective therapeutic agent for the treatment of CDI without damaging the normal gut microbiota.
Keywords: Anti-Bacterial Agents; Bacteriolysis; Bacteriophages; Clostridioides difficile; Clostridium Infections; Endopeptidases; Gastrointestinal Microbiome; Humans; Clostridioides difficile; Endolysin; Gut microbiota; Metagenomics